ANALISIS KESALAHAN DALAM MENGGUNAKAN LAHJAH ARABIYAH PADA MAHARAH KALAM - Maskuri, Maskuri; Miftachul Taubah; Aisyatul Hanun; Nofiyatun Nahilah (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The bacuground of study on this research depends on mistaken in wingArabic dialect that often found in spice skill of islamic student at language room of Ma’had Aly putri which lack of implementation of (pronunciation) of muhadatsah al-yaumiyah eventough the error in using Arabic dialect and teaching languange are two point can’t be separated, those mistakes can be decreased if find the mistakes that was done by language learner. The purpose of this restarch is to know how the speaking ability in spice skill how far the mistaken in speking and what the main factor that caused the error happened. Research method was used by researcher is qualitative and descriptive. data collection techique through observation, interview, and observation. data analyzis technique was used is condensasi data, display data, and verification data. The result of research show that islamic students’ speaking ability in spice skill is good enough. because active social environ ment motivate therr speaking ability to express theis thougt or opinion in using Arabic. Well, the errors in using Arabic dialect often happened in spice skill it’s about element sound that consist of phonology an phonetic. The main factor caused the mistaken are complec, those are the influence of environment, different culture, and no habitual in using dialect of Arabic on muhadatsah al-yaumiyah, not oral Arabic, etc.